Entrepreneurial alertness: Study of the Influence of Individual Characteristics and Entrepreneurship - Hilka Pelizza Vier Machado; Valter da Silva Faia; Juliano Domingues da Silva (BBR: Brazilian Business Review)
ABSTRACT This research tried to understand which statistical variables associated to the individual and the company influence the entrepreneurial alertness. The sample was constituted by 180 entrepreneurs. The entrepreneurial alertness was measured in agreement with the model of Tang, Kacmar and Busenitz (2012). Descriptive statistical tests and normality exam were developed; as well as checked the validity and reliability of the scale through Confirmatory Factor Analysis (CFA). In order to identify the factors that influenced the alertness we developed multiple linear regression and the ANOVA test to determine possible differences among groups (gender, education). The results showed the negative influence of the educational level and the size of enterprises on alertness level; as well as the negative relationship between age and entrepreneurial experience, furthermore, shows that alert level is not determined by gender difference. One of the main implications of this research is to present factors that can potentiate the effects of the entrepreneurial alertness, enlarging the possibilities of identification of opportunities for individuals.